Faktor-Faktor Yang Mempengaruhi Minat Menggunakan Fintech Syariah - Mira Misissaifi; Jaka Sriyana (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
This study aims to identify the factors that influence the interest of the people of Yogyakarta in using Islamic fintech by using the technology acceptance model (TAM). The sampling technique used purposive sampling so that the number of samples obtained was 150 respondents. This study was analyzed using a structural equation model partial least square (SEM-PLS) with the help of SmartPLS 3.2.9 software. The results of this study indicate that the intention to use sharia fintech is influenced by the individual attitude factor towards the presence of sharia fintech. Attitudes to use sharia fintech are influenced by perceived usefulness factors, perceived ease of use, and sharia compliance inherent in sharia fintech. This research can be considered for sharia fintech start-up companies in improving and optimizing the use of sharia fintech.